The bauxite-bearing lateritic profile of the Jequié Complex, São Francisco Craton, Brazil: potential for rare earth elements mineralization and insights on the mineral system - Daniel Augusto de Miranda; Caroline Couto Santos; Fabrício Pereira dos Santos; Anderson Roque Araújo dos Santos Meneses; Carlos Magno Santos Clemente; Rita Oliveira; Isabel Leonor Iza Echeverria Herrera (Journal of the Geological Survey of Brazil, 2023)
The Jequié Block is located at the northeastern portion of the São Francisco Craton and represents the Archean tectonic paleoplate that hosts the Jequié Complex. The rocks of the Jequié Complex are cogenetic, enderbitic-charnockitic plutons, which were intruded by gabbros, norites and anorthosites, and subsequently all these rocks were re-equilibrated in granulite facies. Three bauxite occurrences were mapped at the southeastern portion of the Jequié Block, named Itaji (ITJ), Casa de Farinha (CDF) and Valentim (VLT), which are hosted by the bedrock of the units Poço Preto and Santa Inês – Volta do Rio. The Poço Preto Unit is composed of granulitic granodiorites to tonalities, while Santa Inês – Volta do Rio is composed of granulitic granites to granodiorites. The stream sediment results highlighted good geographic correlation between the content of Al, Fe, REE+Y+Sc and Ce in the catchments at the mineralized area. On the ITJ, the vertical profile indicates a lateritic sequence composed of the bedrock (i), saprock (ii), saprolite (iii) and pedolith (iv), while the upper part is the lateritic duricrust (v). The results of petrography, X-ray powder diffraction and whole rock geochemistry, supports the lateritic evolution. This vertical profile was later redeposited through surficial process in a proximal place. The breakdown of K-feldspar and plagioclase into kaolinite started at the weathering front and was continuously intensified towards the saprolite, as well as the transformation of the biotite and amphibole into goethite. The halloysite was identified as an intermediate mineral between the K-feldspar and kaolinite. The kaolinite locally was represented by its polymorph dickite. The transformation of the kaolinite into gibbsite happened between the saprolite and the pedolith, the main reaction in terms of the mineralization was the pseudomorphic feldspar replacement by gibbsite. The presence of the nordstrandite at CDF could be related to local conditions of the weathering, and/or to the bedrock geochemical composition in the region.